PENGGABUNGAN 2D MOMENT INVARIANT DAN JARINGAN SYARAF TIRUAN UNTUK KLASIFIKASI DAUN TANAMAN ANGGREK - , Nasirudin; , Drs. Agus Harjoko, M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Moment Invariant Based Method or Artifical Neural Network can be used for shape classification individually. This shape classification process still grows and never ends. This research tried to combine both of Moment Invariant and Artificial Neural Network for classification based on shape. This research used orchid leaves plant for the object of the case study. There were four combining models in this research. Based on Moment Invariant, it resulted 85.71% correct answer of all testing samples in this research. Artificial Neural Network also resulted 70.05% correct answer. Then, the four new methods produced the following results: 84.79%, 86.18%, 70.51% and 91.71% correct answer.